2004
DOI: 10.1002/tox.20007
|View full text |Cite
|
Sign up to set email alerts
|

Heavy‐metal and microbial depuration of the clam Ruditapes decussatus and its effect on bivalve behavior and physiology

Abstract: The bivalve Ruditapes decussatus was evaluated as a possible biomonitor of heavy-metal contamination. Concentrations of copper (Cu), cobalt (Co), iron (Fe), nickel (Ni), and manganese (Mn) were measured in R. decussatus. Water and sediment samples were collected at two stations of Timsah Lake in Ismailia, Egypt, from October to November 2002, using atomic absorption spectrophotometry (AAS). Results from the heavy-metal and microbial analyses indicated that site II was less contaminated than site I. The bivalve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
35
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 52 publications
1
35
2
Order By: Relevance
“…This contradiction may be due to the degree of pollution, time of exposure and the molluscan species. Many studies reported the ability of bivalves to accumulate bacteria (Humphrey and Martin, 1993;El-Shenawy, 2004). At the same time, they can purge themselves of bacterial contaminants within 48 h, or they may be held up to 72 h in some cases (Dore and Lees, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This contradiction may be due to the degree of pollution, time of exposure and the molluscan species. Many studies reported the ability of bivalves to accumulate bacteria (Humphrey and Martin, 1993;El-Shenawy, 2004). At the same time, they can purge themselves of bacterial contaminants within 48 h, or they may be held up to 72 h in some cases (Dore and Lees, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, depuration was found to be effective against Salmonella typhimurium after 72 h and Vibrio parahaemolyticus after 36 h in Mytilus galloprovincialis (Barile et al, 2009). El-Shenawy (2004) correlated the depuration of bacteria to the degree of pollution, for example Vibrio was reduced by less than 50% when collected from a heavily polluted site. In Paphia undulata the counts of pathogenic bacteria were reduced by 83% after three days of depuration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations